Antibiotic Prescriptions for Upper Respiratory Infection in the Emergency Department: A Population-Based Study. (10th March 2014) - Hou, Sheng-Wen; Lee, Yi-Kung; Hsu, Chen-Yang; Lee, Ching-Chih; Su, Yung-Cheng
Abstract : Study Objective . Antibiotics prescriptions for upper respiratory infections (URI) are not uncommon, but the benefits for these groups had seldom been evaluated. We aimed to utilize a sampled National Health Insurance (NHI) claims data containing one million beneficiaries to explore if the use of antibiotics could reduce the possibility of unscheduled returns. Methods. We identified patients presented to ambulatory clinics with the discharged diagnoses of URI. The prescriptions of antibiotics were identified. We further matched each patient in the antibiotic group to the patient in the control group by selected covariates using a standard propensity score greedy-matching algorithm. The risks of unscheduled revisits were compared between the two groups. Results. A total of 6915140 visits were identified between 2005 and 2010. The proportions of antibiotics prescriptions are similar among these years, ranging from 9.99% to 13.38 %. In the propensity score assignment, 9190 patients (4595 in each group) were further selected. The odds ratio of unscheduled revisits among antibiotics group and control group was 0.92 (95% CI, 0.70–1.22) with P value equal to 0.569. Conclusions. Overall, antibiotics prescriptions did not seem to decrease the unscheduled revisits in patients presented to the ED with URI. Emergency physicians should reduce the unnecessary prescriptions and save antibiotics to patients with real benefits.